Six students are working to simplify the expression shown. Drag each student's answer to a box to show whether it is fully simplified, equivalent to the given expression but not fully simplified, or not equivalent to the given expression.


Six students are working to simplify the expression shown Drag each students answer to a box to show whether it is fully simplified equivalent to the given expr class=

Respuesta :

The arrows show the appropriate destination for your dragging.

_____

Combining like terms in the given expression makes it simplify to ...

  (2x -18x) +(14y) +(9 -10) = -16x +14y -1

We are to compare this expression with the offered expressions to see if they simplify to the same thing. We'll examine those left-to-right starting with the top row:

  • 2x -18x +14y -19 = -16x +14y -19 . . . not the same
  • -2xy -1 . . . not the same
  • 16x +14y -1 . . . not the same
  • 9 -16x +14y -10 = -16x +14y -1 . . . equivalent
  • -16x +14y -1 . . . equivalent and simplified
  • 2x -18x +14y -1 = -16x +14y -1 . . . equivalent
Ver imagen sqdancefan

Answer:

Here, the given expression,

[tex]9 + 2 x - 18 x + 14 y - 10[/tex]

[tex]= 2 x - 18 x + 14 y - 10 + 9[/tex]

[tex]= (2 - 18 )x + 14 y+ (9 - 10)[/tex]

[tex]= - 16x + 14 y - 1[/tex]

Thus, by the above explanation,

Equivalent and simplified fully = - 16x + 14y -1

Equivalent but not simplified fully = 1) 9 - 16x + 14y-10

2) 2x - 18x + 14y-1

Not equivalent = 1) 2x - 18x + 14 y - 19

2) - 2xy - 1

3) 16x + 14y - 1